Trend of Digital Literacy Skill Research in Communication Education Journals across Indonesia: from Research Design to Data Analysis - Garcia Krisnando Nathanael (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Empowerment of digital literacy skill intends to acquire. This study employed content analysison 36 journal articles that had been published in SINTA (Science and Technology Index), an onlinescientific porta l managed by Ministry of Education, Culture, Research, and Technology of theRepublic of Indonesia, with articles published in 2017 – 2022 with digital literacy as the main focusof the study. This current study has revealed that over the past three years, there has been asignificant increase in the number of publications focusing on research on digital literacy skill. Themajority of the 36 publications the researcher reviewed showed that quantitative researches wereone point or more superior to quantitative research. Additionally, senior high school students wereprimarily selected as the research subjects, with the topic of measuring the level of digital literacyskills being the most popular one. In light of the study's findings, some recommendations have beenmade for additional research. First and foremost, it is essential to improve the research anddevelopment method in order to create more educational materials with the goal of raising teachers'and students' low levels of digital literacy. Second, it is advised that when conducting any research,the researchers choose the test that best fits their hypothesis and research design.